Potensi Nilai Ekonomis Dari Penanganan Sampah Elektrik Dan Peralatan Elektronik Studi Kasus Televisi Cathode Ray Tube - Fikri, Aulia; Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The electronics industry is the fastest growing manufacturing industry in the world, as well as the increasing amount of electrical waste and electronic equipment that has become e-waste. This study refers to the potential economic value of handling e-waste from used television's cathode ray tube, then proceeded to handle using the 3R principle (reduce, reuse and recycle) from disassembling the cathode ray tube, separation of reusable components, and the usage of recycling technology to recycle non-usable components as raw materials for new products. From the utilization stage of e-waste, it can generate economic value from dismantling and recycling process, before going through the process of disassembling the used television's CRT which valued by used goods collectors for Rp.20.000 - Rp. 40.000,- unit. After they had gone through the process of recycling and utilization of electronic components that can be resold, it obtained an increase in economic value 54.7% of the price to buy the television’s CRT waste from used goods collectors, thereby indicating a significant increase in economic value through the recycling of television's CRT so that the e-waste processing can minimize e-waste, and enables a new business field that is quite profitable.Keywords : Cathode Ray Tube, E-waste, Reduce, Recycle, Reuse.